Smart city initiatives in the context of digital transformation : scope, services and technologies - Tomičić-Pupek, Katarina (Array, 2019)
Digital transformation is an emerging trend in developing the way how the work is being done, and it is present in the private and public sector, in all industries and fields of work. Smart cities, as one of the concepts related to digital transformation, is usually seen as a matter of local governments, as it is their responsibility to ensure a better quality of life for the citizens. Some cities have already taken advantages of possibilities offered by the concept of smart cities, creating new values to all stakeholders interacting in the living city ecosystems, thus serving as examples of good practice, while others are still developing and growing on their intentions to become smart. This paper provides a structured literature analysis and investigates key scope, services and technologies related to smart cities and digital transformation as concepts of empowering social and collaboration interactions, in order to identify leading factors in most smart city initiatives.